Pneumonia, an Unusual Initial Presentation of Neonatal Herpes Infection - Franck Kouadio; Gil Klinger (Case Reports in Critical Care)
Neonatal herpes simplex virus (HSV) infection is a life-threatening infection with high morbidity and mortality rates. Neonatal herpes, most commonly due to HSV type 2, is a multi-system disease; however, initial pulmonary presentation is extremely unusual. We describe an infant presenting with progressive respiratory distress, which was the dominant clinical feature of HSV infection during the first days of life. Sepsis work-up and antibiotic treatment were immediately initiated; however, antiviral treatment was not given until the infant’s death. HSV type 1 was isolated in nasopharyngeal and endotracheal aspirates. HSV pneumonia should be considered in a newborn with respiratory deterioration not compatible with common neonatal respiratory diseases.